On bounded positive stationary solutions for a nonlocal Fisher–KPP equation. (January 2015) - Achleitner, Franz; Kuehn, Christian
Abstract: We study the existence of stationary solutions for a nonlocal version of the Fisher–Kolmogorov–Petrovskii–Piscounov (FKPP) equation. The main motivation is a recent study by Berestycki et al. (2009) where the nonlocal FKPP equation has been studied and it was shown for the spatial domain R and sufficiently small nonlocality that there are only two bounded non-negative stationary solutions. Here we provide a similar result for R d using a completely different approach. In particular, an abstract perturbation argument is used in suitable weighted Sobolev spaces. One aim of the alternative strategy is that it can eventually be generalized to obtain persistence results for hyperbolic invariant sets for other nonlocal evolution equations on unbounded domains with small nonlocality, i.e., to improve our understanding in applications when a small nonlocal influence alters the dynamics and when it does not.